The efficacy of neuro-optometric visual rehabilitation therapy in patients with visual snow syndrome - Tsang, Terry; Shidlofsky, Charles; Mora, Vanessa (Frontiers in Neurology, 2022)
This study investigates the efficacy of Neuro-Optometric Rehabilitation Therapy (NORT) for symptom reduction and QOL improvement in patients with VSS using the VFQ-25 Quality of Life Survey. This research provides vital information for all health care professionals who encounter VSS patients by providing an effective treatment option for managing this condition. The study followed the requirements of the Western International Review Board and was compliant with the Health Insurance Portability and Accountability Act. To evaluate if improvements following therapy were statistically significant, participants completed the NEI Visual Function questionnaire 25-2000 edition and performed NORT, administered by a neuro-optometrist or a qualified vision therapist. The NEI-VFQ-25 was conducted before, at six weeks, and at 12 weeks of NORT to evaluate the effects of therapy on VSS symptoms and psychological status. As a generalization for the group of study participants composite and subscale scores – showed improvement, with statistical significance after six and twelve weeks of treatment. As expected, the subscale areas of general health, ocular pain, color vision, and peripheral vision did not show improvement. This demonstrates how NORT efficiently alleviates patients' VSS symptoms and allows patients to perform everyday activities successfully. NORT rehabilitates the visual processing components by decreasing neuroinflammation that contributes to the awareness of VSS symptoms. According to our results and previous research, VSS and its associated abnormal symptoms could be a result of neurological hypersensitivity. As the study was exploratory, the data analysis tools were used for the first time; thus, the required sample size could not be calculated. Additionally, some patients had to discontinue treatment due to COVID-19 pandemic restrictions. It is recommended that future research investigates the influence of genetics, sound modulation therapies, stress reduction techniques, and nutritional considerations in combination with NORT.